The evolution of research and development on cochlear biomodel - Thailis Bounya, Ngelayang; Low, Yin Fen; Rhonira, Latif; Burhanuddin Yeop, Majlis (Penerbit UTM Press, 2016)
The research and development of the cochlear biomodels have initially started over a century ago. Since then, various types of approach have been implemented in trials to perfectly replicate the nature of the human auditory system. The evolution started with the implementation of mechanical elements into the cochlear biomodel operating in air and fluidic surrounding. However, due to the huge size of the mechanical cochlear biomodel, the microelectromechanical systems (MEMS) has been implemented in order to attain a life-sized cochlear biomodel. Researchers have looked into the possibilities of fabricating the MEMS cochlear biomodel in air and fluidic mediums. In this paper, the mechanical and MEMS cochlear biomodel implementations will be reviewed. The key part in modelling the cochlea for human auditory system is to mimic closely its nature and capabilities in terms of the geometrical design, material properties and sensory performance.